Pemanfaatan QR Code Pada Sistem Presensi Dosen Universitas Pamulang Berbasis Mobile Hybrid Menggunakan Framework Flutter - Moh Riza Ari P; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Currently, the recording of the attendance of lecturers and employees at Pamulang University is carried out through a fingerprint attendance system which allows for several obstacles including the risk of spreading the virus COVID-19 (Coronavirus Disease of 2019) because one of the spreads of this virus is holding your nose or mouth without washing your hands first after touching objects. that a person has touched or used COVID-19. Another obstacle to this fingerprint attendance is that the fingerprint machine needs regular maintenance so that the machine always runs optimally, and another obstacle is that fingerprint identification is often hampered when doing attendance. This is because the machine cannot identify dirty fingerprints or there are too many fingerprints attached. The result of this research is a mobile hybrid-based application. By utilizing the QR (Quick Response) code for a mobile hybrid-based attendance system, it aims to provide a solution in addition to breaking the chain of virus spread as well so that attendance can run efficiently. By utilizing the QR (Quick Response) code, lecturers and employees can take attendance by using a camera smartphone for scanning the QR code that has been provided in several places in the campus environment. The system development uses the method Waterfall, and the design uses the UML modeling language.